Comparison of Audiologic Results and Patient Satisfaction for Two Osseointegrated Bone Conduction Devices: Results of a Prospective Study. Issue 5 (June 2015) - Busch, Susan; Giere, Thomas; Lenarz, Thomas; Maier, Hannes
Abstract : Objective: Osseointegrated bone conduction (BC) devices are an important rehabilitation option for patients with mixed or conductive hearing loss or single-sided deafness. The development of new devices is ongoing and requires evaluation of the performance of new hearing aids. Here, we compared the audiologic outcome and subjective benefit of two different designs of osseointegrated implant systems from different manufacturers. Study Design: Prospective, experimental, monocentric, crossover study performed at the Medical University Hannover, Germany. Patients and Interventions: Eleven patients, already implanted with an adequate abutment, tested each device in daily life situations sequentially for a period of 3 weeks. Main Outcome Measures: Bone conduction, word recognition in quiet (Freiburg monosyllable test, L50% ), and speech reception thresholds in noise (Oldenburg Sentence Test) were measured unaided and aided with the devices after each test period. The subjective benefit was assessed by the Abbreviated Profile of Hearing Aid Benefit; the Speech, Spatial and Qualities of Hearing Scale–Comparative questionnaire; and a self-developed handling questionnaire. Results: Audiologic results indicate a slightly better performance of the BCB. However, subjective benefit and patient satisfaction and preference evaluated with questionnaires were higher with the BCP than with the BCB. Conclusion: Amplification-wise, both devices are suitable treatments for hearing-impaired patients. Nevertheless, audiometric tests do not reflect subjective benefit and patients' satisfaction, and both options should be tested to provide each patient with the best possible hearing solution. The study further elucidates the importance and necessity of questionnaires in the process of evaluating the hearing benefit of hearing devices. Abstract : Supplemental digital content is available in the text.